CAMU-CAMU production chain (Myrciaria dubia (Kunth) Mc Vaugh): The case of the producing regions of loreto and Ucayali, Peruvian Amazon - dos Santos, Rodiney Marcelo Braga; Chagas, Pollyana Cardoso; Vieira Rocha, João Henrique de Mello; Chagas, Edvan Alves [UNESP]; Panduro, Mario Herman Pinedo; Lozano, Ricardo Manuel Bardales; Rodriguez, Carlos Abanto (My University, 2018)
Camu-camu (Myrciaria dubia (Kunth) Mc Vaugh) is a shrub fruit tree found on the banks of Amazonian rivers and lakes. Because camu-camu has good agronomic, technological and nutraceutical characteristics, it has a great market potential, mainly due to the high content of ascorbic acid and other active principles found in its fruits. Despite the great importance that camu-camu has for the economy of the regions of Loreto and Ucayali, there are no studies about the organization of the camu-camu productive chain in the Peruvian Amazon, mainly as to its structure, organization and articulation of the agents that constitute the chain. Thus, our aim is to describe the production chain of camu-camu in the above-mentioned regions. For this, the present study was characterized by a qualitative approach of the exploratory-descriptive type and case study, through semi-structured interviews. Data collection was carried out in June and July of 2016. Nineteen interviews were conducted with the agents that were directly or indirectly involved with the camu-camu production chain. In the analysis of the results, it was verified that the low level of the relations between the different agents has led to the configuration of a disordered and fragile chain, resulting in loss of competitiveness of the productive and industrial transformation segments. Based on these findings, the need to formulate public policies that aim to intensify and improve the socio-technical interaction between the links of the productive chain and their respective agents was identified.
Cadeia de produção do CAMU-CAMU (Myrciaria dubia (Kunth) Mc Vaugh): O caso das regiões produtoras de loreto e ucayali na Amazônia Peruana